Membina Dan Membangun Komunitas Berdaya Menuju Era Digital di Padukuhan Sermo Tengah - Al-Raffi, Ariangga Reksa Bima; Al-Rifqi, Imam Faqih; Rosadi, Fais; Efendi, Tasya Radesta; Rahmayanti, Isra’a; Ramadani, Thurfah; Faturrahman, Haifan Eka; Daruseta, Azkia Fiza; Aditianingrum, Trias; Hawa, Salma Tsamrotul; Rahmatullah, Azam Syukur (Universitas Muhammadiyah Yogyakarta, 2025)
The Community Service Program (KKN) in Padukuhan Sermo Tengah, Kalurahan Hargowilis, Kulon Progo Regency, aims to empower the community through education, the development of Micro, Small, and Medium Enterprises (UMKM), and the strengthening of social organizations. The main focus of this program is to improve the ability to read the Al-Qur'an among children in the Al-Qur'an Education Park (TPA) using innovative approaches that involve enjoyable and interactive learning methods. Thus, it is hoped that children will not only be able to read the Al-Qur'an well but also understand the meanings and values contained within it. In addition, this program provides training for UMKM actors in digital marketing and QRIS payment systems. This training aims to enhance the competitiveness of local products in an increasingly competitive market. By utilizing digital technology, it is expected that UMKM actors can reach more consumers and increase their income. A parenting assistance program is also implemented to improve parents' understanding of harmonious parenting patterns. Through discussion sessions and workshops, parents are provided with insights into the importance of good communication within the family and how to support their children's optimal development. The results of these activities demonstrate a high level of enthusiasm from the community. This is reflected in a 75% success rate among 12 participants who consulted parenting experts about child development, a 100% improvement in the understanding of reading Hijaiyah letters, and a 100% increase in MSME competitiveness through the implementation of QRIS. It is hoped that this program will continue and bring broader benefits to the community in the future, fostering sustainable synergy between education, the economy, and social development. With the right support, the people of Sermo Tengah can grow and become self-sufficient in various aspects of life.